Conversion of the Knee Osteoarthritis Outcome Score – Physical Shortform into a Video Format - de Roos, Jordy Anterio (Division of Exercise Science and Sports Medicine, 2019)
Introduction Patient Reported Outcome Measures (PROMs) are an integral part of evidence-based medicine and provide the necessary information for clinicians to make decisions in patient management. The Knee Osteoarthritis Outcome Score-Physical Function Short Form (KOOS-PS) was developed to assess patients’ perception of their knee’s function. Yet, there are cultural and language barriers, when implementing PROMs in a setting for which it was not originally designed, particularly in low-middle income countries with low levels of education. To address these challenges, the study introduces a video version of the KOOS-PS with the aim to validate it in a local setting. Methods This is a validation study of a video version of the KOOS-PS against various other knee scores. The KOOS-PS was converted into videos and a Likert scale in form of icons was used as grading system. The videos were reviewed by a panel for acceptance and comprehensibility. Second, the video score was tested in a prospective study against other internationally accepted and validated knee PROMs. Patients were recruited from both the public and private sectors of healthcare. Descriptive statistics, Pearson’s correlation coefficient and Cronbach’s Alpha were used for psychometric testing. Results The mean time taken to complete the video score was 79 seconds. Internal consistency received an excellent Cronbach’s Alpha of 0.89. Reproducibility received a Pearson Correlation Coefficient of r=0.91 which illustrates there was no significant difference. Pearson Correlation coefficients between the converted video score and other validated scores indicated high correlation. Conclusion This is the first validation study that converts a written PROM into a video format. The results show that the video score is reliable, acceptable, and valid, and can therefore be used in clinical practice.